2023
DOI: 10.1128/spectrum.00023-23
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Investigation of Enteric Virome Signatures from Parental-Generation to Offspring Pigs

Abstract: This study shows that distinct stage-associated swine gut viromes may be determined by age and/or gut physiology at different growth stages, and enteric viruses probably manipulate carbohydrate decomposition by abundant glycoside hydrolases. These findings fill a gap in the longitudinal pattern of the swine gut virome and lay the foundation for research on the function of swine enteric viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…Here, we revealed that gut phages in pigs were predicted to infect a broad range of 14 phyla of prokaryotes, such as Bacteroidota , Bacillota , Pseudomonadota , and Actinomycetota , that were consistent with previous studies on the neonatal piglets [ 48 ] and weaned pigs [ 47 ]. Previous studies showed that gut phages in pigs were predicted to infect several genera of prokaryotes, such as Clostridium , Lactobacillus , Bacillus , Streptococcus , and Bacteroides [ 25 , 52 , 56 , 57 ], that were also consistent with our data. However, previous studies rarely revealed the host species level-taxonomic composition of gut phages in pigs.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we revealed that gut phages in pigs were predicted to infect a broad range of 14 phyla of prokaryotes, such as Bacteroidota , Bacillota , Pseudomonadota , and Actinomycetota , that were consistent with previous studies on the neonatal piglets [ 48 ] and weaned pigs [ 47 ]. Previous studies showed that gut phages in pigs were predicted to infect several genera of prokaryotes, such as Clostridium , Lactobacillus , Bacillus , Streptococcus , and Bacteroides [ 25 , 52 , 56 , 57 ], that were also consistent with our data. However, previous studies rarely revealed the host species level-taxonomic composition of gut phages in pigs.…”
Section: Discussionsupporting
confidence: 92%